Nonlinear dynamics and magneto-elasticity of nanodrums near the phase transition - Makars Šiškins; Ata Keşkekler; Maurits J. A. Houmes; Samuel Mañas-Valero; Maciej Koperski; Eugenio Coronado; Yaroslav M. Blanter; Herre S. J. van der Zant; Peter G. Steeneken; Farbod Alijani (Nature Communications)
Abstract Nanomechanical resonances of two-dimensional (2D) materials are sensitive probes for condensedmatter physics, offering new insights into magnetic and electronic phase transitions. Despite extensive research, the influence of the spin dynamics near a phase transition on the nonlinear dynamics of 2D membranes has remained largely unexplored. Here, we investigate nonlinear magneto-mechanical coupling to antiferromagnetic order in suspended FePS3-based heterostructure membranes. By monitoring the motion of these membranes as a function of temperature, we observe characteristic features in both nonlinear stiffness and damping close to the Néel temperature T N. We account for these experimental observations with an analytical magnetostriction model in which these nonlinearities emerge from a coupling between mechanical and magnetic oscillations, demonstrating that magneto-elasticity can lead to nonlinear damping. Our findings thus provide insights into the thermodynamics and magneto-mechanical energy dissipation mechanisms in nanomechanical resonators due to the material’s phase change and magnetic order relaxation.